Ultrahigh-temperature-resistant and large-temperature-difference-resistant well cementation cement paste as well as preparation method and application thereof
Through specific ratios of cement, quartz sand, silicon powder, water loss-reducing agent and retarder, cementing cement slurry that is resistant to ultra-high temperature and large temperature difference is prepared, which solves the problem that the existing cement slurry cannot meet the cementing needs in complex formation environments. , achieving high strength and stability, ensuring cementing quality and safety.
Patent Information
- Application Number
- CN202411327647.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-23
- Publication Date
- 2025-01-17
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing cement slurry cannot meet the cementing needs in complex formation environments with a bottom-hole temperature of 180-220℃ and a large temperature difference of more than 80℃ between the bottom-hole circulation temperature and the bottom-hole static temperature.
A cement slurry that is resistant to ultra-high temperature and large temperature difference is prepared by using specific contents of cement, quartz sand, silicon powder, water loss reduction agent, retarder and granular silicon. The cementing slurry is formed by forming a mesh structure and retarding through water loss reduction agent. The settling agent extends the settling time, silicon powder and quartz sand improve strength, ensuring the stability of the cementing cement slurry at ultra-high temperatures of 180-220℃ and large temperature difference above 80℃.
The cementing cement slurry is achieved at ultra-high temperatures of 180-220℃ and a large temperature difference of above 80℃, extending the thickening time and ensuring cementing quality and safety.
Smart Images

Figure BDA0005055859480000061 
Figure BDA0005055859480000081 
Figure BDA0005055859480000091
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of oil and gas well cementing, and specifically relates to a cementing slurry resistant to ultra-high temperature and large temperature difference, and a preparation method and application thereof. Background Art
[0002] Deep and ultra-deep oil and gas resources have great potential and have become an important alternative energy source. At present, the drilling investment of deep and ultra-deep wells is huge. The quality of the wellbore is directly related to the success of the drilling project and the life of the oil and gas wells. Cementing is a key technology to ensure the quality of the well project. Cement slurry is the core technology of cementing and an important means to ensure the sustainable and high-quality development of oil and gas field exploration and development. Therefore, it is necessary to further improve the performance of cement slurry.
[0003] CN117735895A discloses a cementing slurry for ultra-high temperature ultra-deep wells, wherein the cementing slurry includes, by weight, oil well cement, reinforcing agent, anti-strength decay agent, dispersant, retarder, fluid loss agent, defoamer and water, and the cementing slurry is suitable for ultra-high temperature ultra-deep well cementing with a bottom hole circulation temperature of 240°C and a bottom hole static temperature of more than 260°C. Under the condition of a bottom hole static temperature of 260°C, the compressive strength of the cement stone is higher than 40MPa and the strength does not decay after 60 days. CN105670582A discloses a large temperature difference resistant cement slurry for oil field cementing, wherein the raw materials for preparing the cement slurry include cement, fluid loss agent, retarder, dispersant and reinforcing agent, and the slurry can be used at a bottom hole temperature of 50-180°C and a temperature difference of 50-70°C between the top of the sealing section and the bottom of the well, and when the top temperature of the sealing section is 70°C, the 48h compressive strength of the cement stone can reach 7.4-9.7MPa.
[0004] The above patents have achieved certain results in the ultra-high temperature resistance and large temperature difference resistance of cement slurry. However, the above cement slurry cannot simultaneously meet the cementing needs in complex formation environments where the bottom hole temperature is 180-220°C and there is a large temperature difference of more than 80°C between the bottom hole circulation temperature and the bottom hole static temperature.
[0005] Therefore, how to develop a cementing slurry that can withstand ultra-high temperatures of 180-220°C and large temperature differences of more than 80°C is a technical problem that needs to be solved urgently in this field. Summary of the invention
[0006] The invention provides a cementing slurry capable of resisting ultrahigh temperature and large temperature difference. The cementing slurry can resist ultrahigh temperature of 180-220°C and large temperature difference of more than 80°C.
[0007] The present invention also provides a method for preparing the cementing slurry. The method has simple process, convenient operation and is convenient for industrial production.
[0008] The present invention also provides a cementing method, which improves the cementing quality and ensures the cementing safety.
[0009] In a first aspect, the present invention provides a cementing slurry resistant to ultra-high temperature and large temperature difference, wherein the cementing slurry comprises the following components in parts by weight: 100-120 parts of cement, 40-47 parts of quartz sand, 10-15 parts of silicon powder, 5-7 parts of fluid loss reducer, 5-7 parts of retarder, 0.1-0.3 parts of granular silicon, and 42-46 parts of water.
[0010] The cement slurry for cementing as described above, wherein the average molecular weight of the fluid loss reducer is 300,000-500,000.
[0011] The cement slurry for cementing as described above, wherein the fluid loss reducer comprises a first copolymer; the monomers forming the first copolymer comprise at least one of 2-acrylamide-2-methylpropane sulfonic acid polymer, 2-acrylamide dodecyl sulfonic acid, and 2-acrylamide-2-phenylethanesulfonic acid.
[0012] The cementing slurry as described above, wherein the average molecular weight of the retarder is 30,000-57,000.
[0013] In the cementing slurry as described above, the retarder comprises a second copolymer, and the monomers forming the second copolymer comprise at least one of 2-acrylamide-2-methylpropane sulfonic acid, N,N-dimethylacrylamide, and 2-acrylamide-2-phenylethanesulfonic acid.
[0014] The cementing slurry as described above, wherein the content of silicon dioxide in the silicon powder is 96%-99.9%.
[0015] The cementing slurry as described above, wherein the particle size of the silicon powder is 300-350 meshes.
[0016] The cementing slurry as described above, wherein the particle size of the quartz sand is 300-350 meshes.
[0017] The cementing slurry as described above, wherein the particle size of the granular silicon is 300-400 mesh.
[0018] The cementing slurry as described above, wherein the cement comprises Class G oil well cement.
[0019] In a second aspect, the present invention provides a cementing method of the above-mentioned cementing slurry, comprising the step of injecting the above-mentioned cementing slurry into a production well through a production casing.
[0020] The implementation of the present invention has at least the following beneficial effects:
[0021] The invention adopts cement, quartz sand, silica powder, fluid loss reducer, retarder, granular silicon and water with specific contents to prepare a cementing slurry resistant to ultra-high temperature and large temperature difference. The cementing slurry can withstand ultra-high temperature of 180-220°C and large temperature difference of more than 80°C. DETAILED DESCRIPTION
[0022] In order to make the purpose, technical solutions and advantages of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0023] The invention provides a cementing slurry capable of resisting ultrahigh temperature and large temperature difference, comprising the following components in parts by weight: 100-120 parts of cement, 40-47 parts of quartz sand, 10-15 parts of silicon powder, 5-7 parts of fluid loss reducer, 5-7 parts of retarder, 0.1-0.3 parts of granular silicon and 42-46 parts of water.
[0024] According to the technical solution of the present invention, a cementing slurry resistant to ultra-high temperature and large temperature difference is prepared by using specific contents of cement, quartz sand, silica powder, fluid loss reducer, retarder, granular silicon and water. The cementing slurry can withstand ultra-high temperature of 180-220°C and large temperature difference of more than 80°C.
[0025] In the present invention, the average molecular weight of the fluid loss reducer is 300,000-500,000, which can form a network structure at high temperature, reduce the filtration loss of cementing slurry under pressure difference, and thus make the cementing slurry resistant to ultra-high temperature of 180-220°C and large temperature difference of more than 80°C.
[0026] In some embodiments, in order to allow the fluid loss additive to form a network structure without thickening at low temperatures (below 50° C.) and without dilution at high temperatures (above 120° C.), the fluid loss additive includes a first copolymer; the monomers forming the first copolymer include at least one of 2-acrylamide-2-methylpropane sulfonic acid, 2-acrylamide dodecyl sulfonic acid, and 2-acrylamide-2-phenylethanesulfonic acid.
[0027] In the present invention, the average molecular weight of the retarder is 30,000-57,000. When the temperature is greater than 150°C, the macromolecular retarder gradually breaks and hydrolyzes to form a small molecular retarder, which prolongs the setting time of the cementing slurry, thereby enabling the cementing slurry to withstand ultra-high temperatures of 180-220°C and large temperature differences of more than 80°C.
[0028] In some embodiments, the retarder includes a second copolymer, and the monomers forming the second copolymer include at least one of 2-acrylamido-2-methylpropane sulfonic acid, N,N-dimethylacrylamide, and 2-acrylamido-2-phenylethanesulfonic acid.
[0029] In the present invention, the content of silicon dioxide in the silicon powder is 96%-99.9%. As a reinforcing agent, the silicon dioxide can prevent the strength of the cementing slurry from declining at 180-220°C.
[0030] Furthermore, the particle size of the silica powder is 300-350 mesh, so that the cementing slurry has higher strength at 180-220°C.
[0031] In the present invention, the particle size of quartz sand is 300-350 meshes. Quartz sand is used as a granular material to form a tight structure with cement and silicon powder through particle grading. The cementing cement slurry is not diluted at 180-220°C, thereby making the cementing cement slurry resistant to ultra-high temperatures of 180-220°C and large temperature differences of more than 80°C.
[0032] In the present invention, the particle size of the granular silicon is 300-400 meshes, and the granular silicon has a large water demand, which can reduce the generation of free liquid in the cementing slurry.
[0033] In the specific implementation of the present invention, the cement includes Class G oil well cement.
[0034] The present invention also provides a method for preparing the cementing slurry, comprising: mixing cement, quartz sand, silica powder, fluid loss reducer, retarder, granular silicon and water in proportion to obtain cementing slurry. The preparation method is simple to operate and is conducive to large-scale promotion and application.
[0035] The present invention also provides a cementing method of the cementing slurry, comprising the step of injecting the cementing slurry into a production well through a production casing. The cementing method is beneficial to improving the cementing quality and ensuring the safety of cementing.
[0036] The sources of raw materials used in the examples and comparative examples of the present invention are as follows:
[0037] Cement: Grade G oil well cement, Zhejiang Jiahua Chemical Co., Ltd.;
[0038] Silica fume: Chaoyang Minghua Mining Co., Ltd.
[0039] Granular silicon: Chaoyang Minghua Mining Co., Ltd.;
[0040] Quartz sand: Chaoyang Minghua Mining Co., Ltd.;
[0041] GWR-300L: Great Wall Drilling and Cementing Company;
[0042] DS-1: Liaoning Hengao;
[0043] DRG: Panjin Hongbo Petroleum Technology Service Co., Ltd.;
[0044] D181: Schlumberger;
[0045] GWF-200L: Great Wall Drilling and Cementing Company.
[0046] The present invention is described in detail below by specific embodiments:
[0047] Example 1
[0048] The preparation method of cementing slurry provided in this embodiment comprises the following steps:
[0049] At 20° C., 100 parts of G-grade oil well cement, 45 parts of quartz sand, 10 parts of silicon powder, 5 parts of DS-1, 5 parts of GWR-300L, 0.1 parts of granular silicon and 42 parts of water were mixed for 50 seconds to obtain the cementing slurry of this embodiment.
[0050] Among them, the particle size of quartz sand is 350 mesh, the content of silicon dioxide in silicon powder is 99%, the particle size of silicon powder is 300 mesh, and the particle size of granular silicon is 350 mesh.
[0051] Example 2
[0052] The preparation method of cementing slurry provided in this embodiment comprises the following steps:
[0053] At 25° C., 100 parts of G-grade oil well cement, 45 parts of quartz sand, 10 parts of silicon powder, 6 parts of DRG, 5 parts of GWR-300L, 0.2 parts of granular silicon and 43 parts of water were mixed for 50 seconds to obtain the cementing slurry of this embodiment.
[0054] Among them, the particle size of quartz sand is 300 mesh, the content of silicon dioxide in silicon powder is 99%, the particle size of silicon powder is 350 mesh, and the particle size of granular silicon is 300 mesh.
[0055] Example 3
[0056] The preparation method of cementing slurry provided in this embodiment comprises the following steps:
[0057] At 15° C., 100 parts of G-grade oil well cement, 45 parts of quartz sand, 10 parts of silicon powder, 7 parts of D181, 6 parts of GWR-300L, 0.3 parts of granular silicon and 44 parts of water were mixed for 50 seconds to obtain the cementing slurry of this embodiment.
[0058] Among them, the particle size of quartz sand is 350 mesh, the content of silicon dioxide in silicon powder is 99%, the particle size of silicon powder is 300 mesh, and the particle size of granular silicon is 400 mesh.
[0059] Example 4
[0060] The preparation method of cementing slurry provided in this embodiment comprises the following steps:
[0061] At 20° C., 100 parts of G-grade oil well cement, 45 parts of quartz sand, 10 parts of silicon powder, 5 parts of GWF-200L, 7 parts of GWR-300L, 0.3 parts of granular silicon and 46 parts of water were mixed for 50 seconds to obtain the cementing slurry of this embodiment.
[0062] Among them, the particle size of quartz sand is 350 mesh, the content of silicon dioxide in silicon powder is 99%, the particle size of silicon powder is 350 mesh, and the particle size of granular silicon is 350 mesh.
[0063] The raw material composition and weight proportions of the ultra-high temperature and large temperature difference resistant cementing slurry provided in Examples 1-4 are shown in Table 1.
[0064] Table 1
[0065]
[0066] Example 5
[0067] The preparation method of cementing cement slurry provided in this embodiment is different from that in Embodiment 1 in that an equal amount of the retarder GWR-300L is replaced by BXR-300L (Tianjin PetroChina Boxing Engineering Technology Co., Ltd.).
[0068] Example 6
[0069] The method for preparing cementing slurry provided in this embodiment is different from that in Embodiment 1 in that an equal amount of quartz sand is replaced with quartz sand with a particle size of 50 mesh (Chaoyang Minghua Mining Co., Ltd.).
[0070] Example 7
[0071] The method for preparing cementing slurry provided in this embodiment is different from that in Embodiment 1 in that an equal amount of granular silicon with a particle size of 350 mesh is replaced by granular silicon with a particle size of 500 mesh.
[0072] Example 8
[0073] The preparation method of cementing slurry provided in this embodiment is different from that in Embodiment 1 in that the content of fluid loss reducer DS-1 is increased from 5 parts to 7 parts, and the content of retarder is reduced from 5 parts to 3 parts.
[0074] Example 9
[0075] The preparation method of cementing slurry provided in this embodiment is different from that in Embodiment 8 in that an equal amount of the fluid loss reducer DS-1 is replaced by DRG.
[0076] Example 10
[0077] The preparation method of cementing slurry provided in this embodiment is different from that in Embodiment 8 in that an equal amount of the fluid loss reducer DS-1 is replaced by D181.
[0078] Embodiment 11
[0079] The preparation method of cementing slurry provided in this embodiment is different from that in Embodiment 8 in that the fluid loss reducer DS-1 is replaced by GWF-200L in equal amount.
[0080] Example 12
[0081] The method for preparing cementing slurry provided in this embodiment is different from that in Embodiment 8 in that a retarder is added so that the content of the retarder is increased to 7 parts.
[0082] Comparative Example 1
[0083] The preparation method of cementing slurry provided in this comparative example is different from that in Example 1 in that an equal amount of quartz sand is replaced by machine-made quartz sand (Panjin Hongbo Petrochemicals).
[0084] Comparative Example 2
[0085] The preparation method of cementing slurry provided in this comparative example is different from that in Example 1 in that an equal amount of silicon powder is replaced by fly ash (Panjin Hongbo Petrochemicals).
[0086] Comparative Example 3
[0087] The preparation method of cementing cement slurry provided in this comparative example is different from that in Example 1 in that an equal amount of granular silicon is replaced by slag particles (Shandong Mingda New Materials Co., Ltd.).
[0088] Performance Testing
[0089] (1) Thickening performance test: The same mass of cement slurries prepared in Examples 1-7 and Comparative Examples 1-3 were weighed and subjected to thickening tests at 220° C. according to the requirements of GB / T10238. The results are shown in Table 2.
[0090] (2) Dosage sensitivity test: The same mass of cement slurries prepared in Examples 8-12 were weighed and subjected to thickening tests at 220° C. according to the requirements of GB / T10238. The results are shown in Table 3.
[0091] (3) Static curing compressive strength: The same mass of cement slurries prepared in Examples 1-7 and Comparative Examples 1-3 were weighed and cured at 100° C., 200° C. and 220° C. for 140 min, respectively, to test the compressive strength of the cement paste. The results are shown in Table 4.
[0092] (4) Compressive strength after curing under temperature difference: The same mass of cement slurries prepared in Examples 1-7 and Comparative Examples 1-3 were weighed and heated to 220° C. for 120 min, maintained at the constant temperature for 20 min, and then cooled to 140° C. to test the compressive strength of the cement paste. The results are shown in Table 4.
[0093] (5) 48h demolding compressive strength: The cement stone was tested using a strength press after 48h demolding. The results are shown in Table 5.
[0094] (6) Compressive strength after 28 days of curing: After demoulding for 48 hours, the cement paste was cured for 28 days to test its compressive strength. The results are shown in Table 5.
[0095] Table 2
[0096]
[0097] According to Table 2, the cement slurries in Examples 1-4 have a relatively long thickening time at 220° C. and have excellent ultrahigh temperature resistance.
[0098] Table 3
[0099]
[0100] It can be seen from Table 3 that the thickening time of the cement slurry in Examples 8-12 is prolonged, and there is a right-angle thickening trend, and the sensitivity response is ideal.
[0101] Table 4
[0102]
[0103] According to Table 4, under a temperature difference of 120° C., the strength of the cement paste formed by demolding the cement slurry in Examples 1-4 does not decline, indicating that the cement paste has excellent stability and sealing integrity at high temperatures.
[0104] Table 5
[0105]
[0106] Note: The “-” in Table 5 indicates that due to the long high-temperature curing time, part of the cement stone cannot be completely demoulded, and the strength of the cement stone is seriously attenuated. The complete cement stone is taken for further cement stone structure test.
[0107] From the analysis of Table 5, it can be seen that the compressive strength of the cement paste in Examples 1-4 after demolding for 48 hours continued to be cured for 28 days without decline, indicating that the cement paste has excellent stability and sealing integrity at high temperature.
[0108] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A cementing slurry resistant to ultra-high temperature and large temperature difference, characterized in that: The cementing slurry comprises the following components in parts by weight: 100-120 parts of cement, 40-47 parts of quartz sand, 10-15 parts of silicon powder, 5-7 parts of fluid loss reducer, 5-7 parts of retarder, 0.1-0.3 parts of granular silicon, and 42-46 parts of water.
2. The cementing slurry according to claim 1, characterized in that: The average molecular weight of the fluid loss reducer is 300,000-500,000.
3. The cementing slurry according to claim 1 or 2, characterized in that: The fluid loss additive comprises a first copolymer; the monomers forming the first copolymer comprise at least one of 2-acrylamide-2-methylpropane sulfonic acid, 2-acrylamide dodecyl sulfonic acid and 2-acrylamide-2-phenylethane sulfonic acid.
4. The cementing slurry according to any one of claims 1 to 3, characterized in that: The average molecular weight of the retarder is 30,000-57,000.
5. The cementing slurry according to any one of claims 1 to 4, characterized in that: The retarder comprises a second copolymer, and the monomers forming the second copolymer comprise at least one of 2-acrylamide-2-methylpropane sulfonic acid, N,N-dimethylacrylamide, and 2-acrylamide-2-phenylethanesulfonic acid.
6. The cementing slurry according to any one of claims 1 to 5, characterized in that: The content of silicon dioxide in the silicon powder is 96%-99.9%; The particle size of the silicon powder is 300-350 meshes.
7. The cementing slurry according to any one of claims 1 to 6, characterized in that: The particle size of the quartz sand is 300-350 meshes.
8. The cementing slurry according to any one of claims 1 to 7, characterized in that: The particle size of the granular silicon is 300-400 meshes.
9. The cementing slurry according to any one of claims 1 to 8, characterized in that: The cement includes Class G oil well cement.
10. A cementing method, characterized in that: The method comprises the step of injecting the cementing slurry according to any one of claims 1 to 9 into the production well through the production casing.
Citation Information
Patent Citations
Well cementation cement paste for ultra-high-temperature ultra-deep well and preparation method of well cementation cement paste
CN117735895A
Preparation method of high-temperature-resistant great-temperature-difference cement paste for oilfield well cementing
CN105670582A
High-temperature-resistant polymerization suspension stabilizer cement paste for oil well cement and preparation method thereof
CN113736016A
Large-temperature-difference well cementation cement paste and preparation method thereof
CN114380540A
Single-stage well cementation anti-upside-down high-temperature large-temperature-difference cement paste system
CN118598587A
Cited By
High-performance well cementation cement system for deep geothermal development
CN120590100A